(3GdeHgLs - (3YHO Gdedc Hf eMeO Hf ESeGYjd, CHh efUhQ GdKYGdHj,J (B429 (3g` s
(3ChdgG (B:s
(3gPG cJGH YhdJ ajg Ydi NhGWQi dG OaGJQi hYdi ebhdi dG Ydi efbhdi , hYdi acQi dG Ydi PcQi CdN s
(3Cdag ddCejQ TeS GdOjf bHhS Hf CHj WGgQs
(3QJHg Ydi SHYjf HGHkG hLeY ajg CcKQ ef Cda cdeI LQJ eLQi GdCeKGds
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B163 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B189s
Keywords: (3GdCOHs